(untitled) (Journal of Namibian Studies : History Politics Culture, 2024)
The unique silver ornaments of the Miao nationality in Guangxi, China reflect the specific characteristics of the times and cultural background. With the change of environment and the development of Internet economy, the protection and development policies of Miao silver jewelry are also changing. Service design is a new extension of the traditional design field in the post-industrial era, and it is an all-round realization of the design process. This study aims to solve the development mode of traditional Guangxi Miao silver jewelry craft in modern society, propose the strategic design of transformation from traditional product design mode to cultural service with the concept of service design, and explore the innovative strategy of traditional silver jewelry product design. Through case analysis, using the design thinking and methods in service design, starting from the service design process, construct the process of design stage of Miao silver jewelry products in Guangxi, and based on the characteristics of different stages, integrate KANO model and consumer satisfaction analysis method, finally review the process objectives and application process of service design stage, Construct the design process model of Miao silver jewelry product service based on design thinking from three levels of instinct layer, functional layer and reflection layer, explore the conservation strategies of traditional silver jewelry techniques, enhance the social and cultural value of traditional silver jewelry, bring new opportunities for the design of traditional silver jewelry products, better promote the development of traditional culture.